Tracing the Roots of Inquiry: A Historical Review of Nursing Research Through Professionalisation Theory - Raghad Almushawah; Dilla Davis; Ehsan Khan (Nursing Inquiry, 2026)
ABSTRACT Nursing research has developed unevenly across history, shaped by shifting institutional structures, professional aspirations and societal demands. Yet existing historical reviews have largely adopted descriptive approaches, while few have applied an explicit theoretical lens to explain why this unevenness persists. This paper addresses that gap by examining the historical development of nursing research through Greenwood's trait‐based professionalisation framework. Drawing on a narrative historical review spanning seven chronological periods, the analysis reveals a recurring pattern of partial professionalisation ; nursing has consistently generated specialised knowledge yet has struggled to secure organisational infrastructure to embed and control that knowledge within clinical practice. The historical analysis suggests that knowledge production alone within a profession does not guarantee epistemic control.